2016
DOI: 10.3389/fpls.2016.01605
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis and Accumulation of Resveratrol Are Associated with Veraison and Abscisic Acid Concentration in Beihong (Vitis vinifera × Vitis amurensis) Berry Skin

Abstract: Resveratrols are polyphenolic secondary metabolites that can benefit human health, and only occur in a few plant families including Vitaceae. It has been reported that abscisic acid (ABA) can induce veraison (the onset of grape berry ripening) and may induce the accumulation of resveratrol in berry skin. However, the relationships between ABA, veraison, the accumulation of anthocyanins and the accumulation of resveratrol in the berry are poorly understood. This study attempted to answer this question through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Comprehensive studies have shown that ABA is an important hormone in the inception and color development stage of grape berries ripening ( Ferrara et al, 2015 ; Fortes et al, 2015 ; Jia et al, 2017 ; Pilati et al, 2017 ). A strong rise in berry ABA content corresponds with the increase in total anthocyanin content that is recorded around the véraison and during the initial stages of ripening ( Wheeler et al, 2009 ; Lacampagne et al, 2010 ; Sun et al, 2010 ; Wang et al, 2016 ). Anthocyanins keep increasing throughout the ripening phase, while ABA levels simultaneously start to decrease ( Wheeler et al, 2009 ; Wang et al, 2016 ), implying that ABA triggers but does not necessarily maintain color acquisition ( Kuhn et al, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Comprehensive studies have shown that ABA is an important hormone in the inception and color development stage of grape berries ripening ( Ferrara et al, 2015 ; Fortes et al, 2015 ; Jia et al, 2017 ; Pilati et al, 2017 ). A strong rise in berry ABA content corresponds with the increase in total anthocyanin content that is recorded around the véraison and during the initial stages of ripening ( Wheeler et al, 2009 ; Lacampagne et al, 2010 ; Sun et al, 2010 ; Wang et al, 2016 ). Anthocyanins keep increasing throughout the ripening phase, while ABA levels simultaneously start to decrease ( Wheeler et al, 2009 ; Wang et al, 2016 ), implying that ABA triggers but does not necessarily maintain color acquisition ( Kuhn et al, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
“…A strong rise in berry ABA content corresponds with the increase in total anthocyanin content that is recorded around the véraison and during the initial stages of ripening ( Wheeler et al, 2009 ; Lacampagne et al, 2010 ; Sun et al, 2010 ; Wang et al, 2016 ). Anthocyanins keep increasing throughout the ripening phase, while ABA levels simultaneously start to decrease ( Wheeler et al, 2009 ; Wang et al, 2016 ), implying that ABA triggers but does not necessarily maintain color acquisition ( Kuhn et al, 2014 ). Additionally, treatments by ABA cause an advance in red color development including Olympia ( Hiratsuka et al, 2001a ), Kyoho ( Ban et al, 2003 ), Crimson Seedless ( Cantin et al, 2007 ; Ferrara et al, 2013 ), Cabernet Sauvignon ( Wheeler et al, 2009 ), Alicante Bouschet ( Castellarin et al, 2011 ) and Fujiminori ( Jia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 86%
“…Abscisic acid may trigger the onset of grape fruit ripening and may lead to accumulation of RSV in the skin. Whereas anthocyanins concentration increased irrespectively of the maturation stage at which the acid was added, the concentration of the STB only increased when the compound was added nearly before or at veraison (or onset of ripening) (Wang et al., ). The same study, which was performed in Beihong ( Vitis amurensis/Vitis vinifera ) grapes, showed that in natural conditions, that is, in the absence of abscisic acid, the STB content in berry skin was progressively increased with maximal levels obtained upon full maturation.…”
Section: Post‐harvest Methods Affecting the Stb Content Of Winementioning
confidence: 99%
“…However, this synthesis gradually decreased, which was explained by the regulation of stilbene synthase, the key enzyme in resveratrol biosynthesis, by the transcription factor MYB14 . The same authors also revealed that the concentration of this constituent increased in the berry skin of the same species during exogenous application of ABA 10 days before veraison or at veraison [ 61 ].…”
Section: General Information On Berry-derived Polyphenolsmentioning
confidence: 99%